Enantiomer separation of [60]fullerene derivatives by micro-column high- performance liquid chromatography using (R)-(-)-2-(2,4,5,7-tetranitro-9- fluorenylideneaminooxy) propionic acid as chiral stationary phase - Gross, Birgit; Schurig, V.; Lamparth, Iris; Hirsch, Andreas (Journal of Chromatography A, 1997)
The enantiomer separation of [60]fullerene derivatives on the chiral stationary phase (CSP) (R)-(-)-2-(2,4,5,7-tetranitro-9- fluorenylideneaminooxy) propionic acid (TAPA) was achieved. A [60]fullerene tris- and hexakis-adduct with achiral addends and an inherent chiral addition pattern were separated on a micro HPLC column containing R-(-)-TAPA bonded to silica gel as CSP. The stationary phase exhibits an intermediate polarity and separations were performed using the normal and reversed-phase mode. With the hexakis-adduct, near-baseline separation was achieved. The tris-adduct shows a strong interaction with the CSP expressed by a high retention factor but inferior enantiomer separation.